Quality of training in cervical cancer radical surgery: a survey from the European Network of Young Gynaecologic Oncologists (ENYGO) - Bizzarri, Nicolò; Pletnev, Andrei; Razumova, Zoia; Zalewski, Kamil; Theofanakis, Charalampos; Selcuk, Ilker; Nikolova, Tanja; Lanner, Maximilian; Gómez-Hidalgo, Natalia R; Kacperczyk-Bartnik, Joanna; Querleu, Denis; Cibula, David; et al. (International journal of gynecological cancer, 2022)
BACKGROUND: The European Society of Gynaecological Oncology (ESGO) and partners are committed to improving the training for gynecologic oncology fellows. The aim of this survey was to assess the type and level of training in cervical cancer surgery and to investigate whether the Laparoscopic Approach to Cervical Cancer (LACC) trial results impacted training in radical surgery for gynecologic oncology fellows. METHODS: In June 2020, a 47-question electronic survey was shared with European Network of Young Gynaecologic Oncologists (ENYGO) members. Specialist fellows in obstetrics and gynecology, and gynecologic oncology, from high- and low-volume centers, who started training between January 1, 2017 and January 1, 2020 or started before January 1, 2017 but finished their training at least 6 months after the LACC trial publication (October 2018), were included. RESULTS: 81 of 125 (64.8%) respondents were included. The median time from the start of the fellowship to completion of the survey was 28 months (range 6-48). 56 (69.1%) respondents were still fellows-in-training. 6 of 56 (10.7%) and 14 of 25 (56.0%) respondents who were still in training and completed the fellowship, respectively, performed ≥10 radical hysterectomies during their training. Fellows trained in an ESGO accredited center had a higher chance to perform sentinel lymph node biopsy (60.4% vs 30.3%; p=0.027). There was no difference in the mean number of radical hysterectomies performed by fellows during fellowship before and after the LACC trial publication (8±12.0 vs 7±8.4, respectively; p=0.46). A significant reduction in number of minimally invasive radical hysterectomies was noted when comparing the period before and after the LACC trial (38.5% vs 13.8%, respectively; p<0.001). CONCLUSION: Exposure to radical surgery for cervical cancer among gynecologic oncology fellows is low. Centralization of cervical cancer cases to high-volume centers may provide an increase in fellows' exposure to radical procedures. The LACC trial publication was associated with a decrease in minimally invasive radical hysterectomies performed by fellows.
Keywords: surgical oncology; nádory děložního čípku; Oncologists; cervical cancer; Surveys and Questionnaires; Uterine Cervical Neoplasms; Humans; Female; COVID-19; Medical Oncology; gynecologic surgical procedures; ženské pohlaví; průzkumy a dotazníky; Education, Medical, Graduate; hysterectomy; studium lékařství specializační postgraduální; lékařská onkologie; onkologové; lidé